10.1016/s1544-8800(06)70731-x (CrossRef Listing of Deleted DOIs, 2000)
AIM: To explore the positioning of the Professional Doctorate in Nursing within contemporary nursing education, particularly in Australia and Aotearoa New Zealand, and examine how institutional structures influence its recognition, contribution and potential to strengthen healthcare leadership and practice-focused scholarship. DESIGN: Discursive paper. METHODS: Not applicable. RESULTS: This discursive paper draws on contemporary literature relating to doctoral education, professional doctorates, nursing leadership, and higher education, together with the authors' collective experience in graduate research leadership, doctoral supervision, professional doctorate education, and clinical-academic partnerships within Australia and Aotearoa New Zealand. Drawing on Institutional Theory as a conceptual lens, the paper argues that the uneven recognition of professional doctorates reflects institutional norms, reward systems, and historical conceptions of doctoral scholarship rather than limitations of the qualification itself. International developments are examined to demonstrate how differing educational and professional contexts influence the positioning of professional doctorates and their contribution to nursing and healthcare. CONCLUSION: Professional doctorates represent an important, yet under-recognised, form of doctoral scholarship that complements the traditional Doctor of Philosophy (PhD) by integrating rigorous doctoral research with evidence implementation, clinically embedded scholarship, leadership, and healthcare improvement. Greater institutional value of both doctoral pathways may better align doctoral education with the evolving needs of contemporary healthcare. IMPLICATIONS FOR NURSING: Recognising PhD and professional doctorates as both forms of doctoral scholarship has important implications for universities, healthcare organisations, professional bodies, and policymakers. Broader recognition of implementation-focused scholarship may strengthen clinically embedded leadership, evidence translation, workforce capability and healthcare innovation while supporting more diverse doctoral career pathways.